Chitosan-based systems aimed at local application for vaginal infections. (1st June 2021) - Araujo, Victor Hugo Sousa; de Souza, Maurício Palmeira Chaves; Carvalho, Gabriela Corrêa; Duarte, Jonatas Lobato; Chorilli, Marlus
Graphical abstract: Highlights: Mucoadhesive systems for vaginal administration. Mucoadhesive systems composed of chitosan. Mucoadhesive systems composed of chitosan intended for the treatment of infectious vaginal diseases. Abstract: Vaginal administration is a promising route for the local treatment of infectious vaginal diseases since it can bypass the first-pass metabolism, drug interactions, and adverse effects. However, the commercial products currently available for topical vulvovaginal treatment have low acceptability and do not adequately explore this route. Mucoadhesive systems can optimize the efficacy of drugs administered by this route to increase the retention time of the drug in the vaginal environment. Several polymers are used to develop mucoadhesive systems, among them chitosan, a natural polymer that is highly biocompatible and technologically versatile. Thus, the present review aimed to analyze the studies that used chitosan to develop mucoadhesive systems for the treatment of local vaginal infections. These studies demonstrated that chitosan as a component of mucoadhesive drug delivery systems (DDS) is a promising device for the treatment of vaginal infectious diseases, due to the intrinsic antimicrobial activity of this biopolymer and because it does not interfere with the effectiveness of the drugs used for the treatment.